Detection of odoriferous subgingival and tongue microbiota in diabetic and nondiabetic patients with oral malodor using polymerase chain reaction - Dinesh R Kamaraj; Kala S Bhushan; Vandana K Laxman; John Mathew (Wolters Kluwer Medknow Publications, 2011)
Background: Halitosis has been correlated with the concentration of volatile sulfur compounds (VSCs) produced in the oral cavity by metabolic activity of bacteria colonizing the periodontal pockets and the dorsum of the tongue. It has been assumed that there is a relationship between periodontal disease and diabetes mellitus. Objectives: The aim of the study was to assess the malodor using the organoleptic method and tanita device; to quantify odoriferous microorganisms of subgingival plaque and tongue coating, such as P. gingivalis (Pg), T. forsythia (Tf), and F. nucleatum (Fn) using polymerase chain reaction (PCR) in nondiabetic and diabetic chronic periodontitis patients. Patients and Methods: Thirty chronic periodontitis patients (with and without diabetes) with 5-7 mm pocket depth, radiographic evidence of bone loss, and presence of oral malodor participated in this study. Subjective assessment of mouth air was done organoleptically and by using a portable sulfide monitor. Tongue coating was also assessed. Results: The scores of plaque index, gingival index, gingival bleeding index, VSC levels, and tongue coating between the nondiabetic and diabetic patients were not significant (P>0.5). In nondiabetic patients, Fn was found to be significantly (P<0.5) more in tongue samples, whereas Pg and Tf have not shown significant values (P>0.5). In diabetic patients, Fn and Tf have shown significant (P<0.5) an increase in subgingival and tongue samples, respectively, whereas Pg has not shown significant difference between subgingival and tongue samples. Interpretation and Conclusion: The results confirm that there is no difference in clinical parameters between nondiabetic and diabetic periodontitis patients, but the odoriferous microbial profiles in tongue samples of diabetic patients were found to be high. However, there is a weak positive correlation between VSC levels, clinical parameters, and odoriferous microbial profiles.